Self-efficacy and performance of the roundhouse kick in taekwondo (Revista de Artes Marciales Asiáticas, 2014)
Development of self-efficacy scales allows the analysis of athletes’ perceptions and examination of the relationship between perception and performance. The aim of this paper was to: (1) develop a specific self-efficacy scale in a taekwondo task, the roundhouse kick, and (2) analyse the sport performance and its relationship with two self-efficacy scales (specific and general) outcomes according to the athletes’ gender. Forty-three taekwondo athletes (33 male and 10 female) participated in this study. The Physical (PSE) and Specific (RKSES) self-efficacy scales were administered. Performance data (impact force and total response time) were acquired by athletes kicking twice to an instrumented target. Results showed that the specific self-efficacy scale has high reliability and is able to predict sport performance in males and females. Males had higher self-efficacy scores and also higher performance results than females. Females’ taekwondo psychological training should be focus on improving their self-efficacy perception in order to increase their performance in the roundhouse kick. This specific self-efficacy scale for the taekwondo roundhouse kick offers empirical information to coaches, sport psychologists and researchers that allow them to predict athletes’ sport performance in the roundhouse kick.